Low glucose but not galactose enhances oxidative mitochondrial metabolism in C2C12 myoblasts and myotubes - Elkalaf, Moustafa; Anděl, Michal; Trnka, Jan (PloS one, 2013)
BACKGROUND: Substituting galactose for glucose in cell culture media has been suggested to enhance mitochondrial metabolism in a variety of cell lines. We studied the effects of carbohydrate availability on growth, differentiation and metabolism of C2C12 myoblasts and myotubes. METHODOLOGY/PRINCIPAL FINDINGS: We measured growth rates, ability to differentiate, citrate synthase and respiratory chain activities and several parameters of mitochondrial respiration in C2C12 cells grown in media with varying carbohydrate availability (5 g/l glucose, 1 g/l glucose, 1 g/l galactose, and no added carbohydrates). C2C12 myoblasts grow more slowly without glucose irrespective of the presence of galactose, which is not consumed by the cells, and they fail to differentiate without glucose in the medium. Cells grown in a no-glucose medium (with or without galactose) have lower maximal respiration and spare respiratory capacity than cells grown in the presence of glucose. However, increasing glucose concentration above physiological levels decreases the achievable maximal respiration. C2C12 myotubes differentiated at a high glucose concentration showed higher dependency on oxidative respiration under basal conditions but had lower maximal and spare respiratory capacity when compared to cells differentiated under low glucose condition. Citrate synthase activity or mitochondrial yield were not significantly affected by changes in the available substrate concentration but a trend towards a higher respiratory chain activity was observed at reduced glucose levels. CONCLUSIONS/SIGNIFICANCE: Our results show that using galactose to increase oxidative metabolism may not be applicable to every cell line, and the changes in mitochondrial respiratory parameters associated with treating cells with galactose are mainly due to glucose deprivation. Moderate concentrations of glucose (1 g/l) in a growth medium are optimal for mitochondrial respiration in C2C12 cell line while supraphysiological concentrations of glucose cause mitochondrial dysfunction in C2C12 myoblasts and myotubes.
Keywords: Glycolysis; Culture Media; Galactose; Cell Line; Cell Respiration; glukosa; galaktosa; Cell Differentiation; Electron Transport; Mitochondria, Muscle; buněčné dýchání; Electron Transport Chain Complex Proteins; kosterní svalová vlákna; Mice; Oxidation-Reduction; transport elektronů; myoblasty kosterní; Muscle Fibers, Skeletal; zvířata; elektronový transportní řetězec; svalové mitochondrie; glykolýza; kultivační média; Myoblasts, Skeletal; myši; oxidace-redukce; buněčné linie; buněčná diferenciace; Glucose; Animals